Measurement of Complex Permittivity and Permeability Through a Cavity- Perturbation Method - Rydholm, Tomas (My University, 2015)
Fabrication of antenna and microwave devices demands good knowledge of certain material parameters such as permittivity and permeability, including their corresponding losses. The project presented in this master’s degree thesis aims to develop an experimental setup to measure these properties at microwave frequencies. A cylindrical cavity resonator was designed for a cavity perturbation method. In this method, it is studied how the resonance frequencies shift as a sample is inserted into the cavity resonator. The permittivity and permeability can be determined from this frequency shift and the loss parameters can be obtained from the broadening of the resonance peaks in the spectrum. An alternative method is developed, in which the measurements are compared to data obtained from simulations. A set of curves or contour lines, describing the resonance frequency of a specified mode, is plotted as function of the permittivity and permeability. By performing two measurements where the sample is placed at two different positions in the cavity, the material properties can be determined from the point where the two curves cross each other. We refer to this new method as the “curve-set method”. Simulations indicate that the cavity-perturbation method can be used together with the designed cavity resonator to measure the permittivity and dielectric loss tangent accurately for nonmagnetic materials. However, it seems difficult to measure the permeability and magnetic loss tangent. On the other hand, the curve-set method appears to be a possible way to determine both the permittivity and the permeability, given that the simulations represent experiments accurately.
Keywords: permittivity; permeability; dielectric loss; magnetic loss; cavity resonator; resonance frequency; cavity-perturbation method